IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PESANTREN SEKOLAH DI SMK MA’ARIF 1 KEBUMEN - alfiyan naufary (Jurnal Penelitian Agama, 2015)
Abstract: The results of this study indicate that the process of implementation of character education through vocational boarding school in Maarif 1 Kebumen showed 9 characters embedded in the school through fomal and non-fomal schools provide character education to leamers. These activities include: jama'ah fard prayer, recitation of books, reading the Koran, follow the teaching of English, khitobah and voluntary work on Sundays, as well as through the method of waming, modeling, and methods of habituation. Keywords: Implementation, Character Education, Pesantren.